Jo Davidson papers - Davidson, Jo, 1883-1952.; Davidson, Jo, 1883-1952.
Correspondence, speeches, writings, articles, notes, clippings, photographs, and other papers relating to Davidson's career as a portrait sculptor and to his activities as cochairman of the Progressive Citizens of America and chairman of the National Wallace for President Committee. Includes individual files on many of Davidson's sculptures and a draft of Between Sittings; An Informal Autobiography (1951). Family correspondents include his first wife, Yvonne Davidson; second wife, Florence Lucius Davidson; and his sons, Jean Davidson and Yvon Jacques Davidson. Other correspondents include Helen Keller, Lincoln Steffens, Frank Swinnerton, and Henry A. Wallace.
Sculptor. Full name: Joseph Davidson.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Davidson, Yvonne, -- -1934 -- Correspondence; Davidson, Florence Lucius, -- -1962 -- Correspondence; Davidson, Yvon Jacques, -- 1910- -- Correspondence; Davidson, Jean, -- 1914- -- Correspondence; Keller, Helen, -- 1880-1968 -- Correspondence; Steffens, Lincoln, -- 1866-1936 -- Correspondence; Swinnerton, Frank, -- 1884-1982 -- Correspondence; Wallace, Henry A. -- 1888-1965.; Wallace, Henry A. -- 1888-1965 -- Correspondence; Davidson family; Progressive Citizens of America; National Wallace for President Committee; Progressivism (United States politics); Art; Portrait sculpture; Sculpture; Presidents -- United States -- Election -- 1948.; United States -- Politics and government -- 1945-1953.; Artists; Sculptors